The safety and effectiveness of the Woven EndoBridge (WEB) system for the treatment of wide-necked bifurcation aneurysms: final 12-month results of the pivotal WEB Intrasaccular Therapy (WEB-IT) Study - (:unkn) unknown (BMJ PUBLISHING GROUP, 2019)
Introduction The Woven EndoBridge Intrasaccular Therapy (WEB-IT) Study is a pivotal, prospective, singlearm, investigational device exemption study designed to evaluate the safety and effectiveness of the WEB device for the treatment of wide-neck bifurcation aneurysms. Methods One-hundred and fifty patients with wideneck bifurcation aneurysms were enrolled at 21 US and six international centers. Angiograms from the index procedure, and 6-month and 1-year follow-up visits were all reviewed by a core laboratory. All adverse events were reviewed and adjudicated by a clinical events adjudicator. A data monitoring committee provided oversight during the trial to ensure subject safety. Results One-hundred and forty-eight patients received the WEB implant. One (0.7%) primary safety event occurred during the study-a delayed ipsilateral parenchymal hemorrhage-on postoperative day 22. No primary safety events occurred after 30 days through 1 year. At the 12-month angiographic follow-up, 77/143 patients (53.8%) had complete aneurysm occlusion. Adequate occlusion was achieved in 121/143 (84.6%) subjects. Conclusions The prespecified safety and effectiveness endpoints for the aneurysms studied in the WEB-IT trial were met. The results of this trial suggest that the WEB device provides an option for patients with wide-neck bifurcation aneurysms that is as effective as currently available therapies and markedly safer.
Keywords: PIPELINE EMBOLIZATION DEVICE; STENT-ASSISTED COILING; INTRACRANIAL ANEURYSMS; CEREBRAL ANEURYSMS; ENDOVASCULAR TREATMENT; FOLLOW-UP; COMPLICATIONS; COHORT